Course Content
第4章:坐标变换
高三数学 | 高级数学
About Lesson

2.3 Inverse Trigonometry Function Identities 反三角函数的恒等式


Prove the following inverse trigonometry statements
试证明下列各反三角函数式

1) \tan^{-1}{\frac{4}{3}}+\sin^{-1}{\frac{12}{13}}=\cos^{-1}{\left(-\frac{33}{65}\right)}

2) \sin^{-1}{\frac{4}{5}}+\cos^{-1}{\frac{12}{13}}=\tan^{-1}{\frac{63}{16}}

3) {cos}^{-1}{\frac{3}{5}}+{tan}^{-1}{\frac{5}{12}}={tan}^{-1}{\frac{63}{16}}

4) {cos}^{-1}{\frac{3}{5}}+{sin}^{-1}{\frac{12}{13}}=\pi-{sin}^{-1}{\frac{56}{65}}

5) 2{tan}^{-1}{\frac{1}{3}}={tan}^{-1}{\frac{3}{4}}

6) \sin^{-1}{\frac{3}{5}}+\sin^{-1}{\frac{8}{17}}=\sin^{-1}{\frac{77}{85}}

Exercise Files
No Attachment Found
No Attachment Found